O sistema financeiro globalizado contemporâneo: Estrutura e perspectivas - Ernani Teixeira Torres Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The paper analyzes the development of the contemporary globalized financial system as a consequence of the innovations introduced by private markets, but mostly the strategy of the governments, particularly the US. This new global financial system, based on the floating dollar, generated many financial bubbles since it was consolidated in the 1980s. The crisis of 2008 is the latest and the greatest of them, because it negatively affected the major banks of the main market of the system, the United States. Its origin is related to the changes that occurred in the business strategies of these banks. They left aside their traditional lending activities to businesses and families in favor of more speculative investments, based on high leverage ratios, thus adopting a behavior similar to what hedge funds do.
Keywords: E44; F65; G15; N20; 330; financial globalization; international financial crisis; financial regulation